Describing motion events - Gerwien, Johannes; Stutterheim, Christiane von (Handbooks of Pragmatics [HOPS] ; 14: Pragmatics of space, 2022)
Das Kapitel 6. Describing motion events erschien in Pragmatics of Space auf Seite 153.
Gesehen am 13.09.2022